Within-Subject Variability and the Influence of Exercise Training History on the Resting Plasma Metabolome in Men - Darragh, Ian A J; O'Driscoll, Lorraine; Egan, Brendan (International journal of sport nutrition and exercise metabolism, 2023)
This study investigated within-subject variability in the circulating metabolome under controlled conditions, and whether divergent exercise training backgrounds were associated with alterations in the circulating metabolome assessed in resting samples. Thirty-seven men comprising of endurance athletes (END; body mass, 71.0 ± 6.8 kg; fat-free mass index, 16.9 ± 1.1 kg/m2), strength athletes (STR; 94.5 ± 8.8 kg; 23.0 ± 1.8 kg/m2), and recreationally active controls (CON; 77.6 ± 7.7 kg; 18.1 ± 1.0 kg/m2) provided blood samples after an overnight fast on two separate occasions controlled for time of day of sampling, recent dietary intake, time since last meal, and time since last exercise training session. A targeted profile of metabolites, performed using liquid chromatography and mass spectrometry on plasma samples, identified 166 individual metabolites and metabolite features, which were analyzed with intraclass correlation coefficients, a multilevel principal component analysis, and univariate t tests adjusted for multiple comparisons. The median intraclass correlation coefficient was .49, with 46 metabolites displaying good reliability and 31 metabolites displaying excellent reliability. No difference in the abundance of any individual metabolite was identified within groups when compared between visits, but a combined total of 44 metabolites were significantly different (false discovery rate <0.05) between groups (END vs. CON, 42 metabolites; STR vs. CON, 10 metabolites; and END vs. STR, five metabolites). Under similar measurement conditions, the reliability of resting plasma metabolite concentrations varies largely at the level of individual metabolites with ∼48% of metabolites displaying good-to-excellent reliability. However, a history of exercise training was associated with alterations in the abundance of ∼28% of metabolites in the targeted profile employed in this study.